Assessment of musical interventions and its effect on blood pressure among United States populations: a systematic review and meta-analysis - Meda, Shreya; Gyamfi, Joyce; Patel, Kahini; Islam, Farha; Vieira, Dorice; Nyame, Solomon; Ruan, Christina; Boradia, Krupa; Chhetri, Himani; Thunga, Sukruthi; Adenikinju, Deborah; Amesimeku, Etornam; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Hypertension (HTN) currently affects over 120 million Americans, in the United States (US). Thus, the implementation of evidence-based interventions (EBI) for blood pressure (BP) reduction is pivotal in minimizing this burden. We sought to evaluate evidence from published literature on the effectiveness of musical interventions for BP reduction within the US.Methods: A systematic review of studies that utilize music interventions to manage BP was conducted in October of 2022. An extensive search of several databases utilizing MeSH terms and relevant keywords was conducted for articles published through October 2022. An updated search was conducted in October 2023 to identify additional studies.Results: 2381 studies were screened for title/abstract relevancy. 1885 studies were deemed irrelevant, and 495 studies were examined for full-text review; of which 384 were excluded due to being non-US-based. Overall, 25 studies were found where BP was the primary outcome and discussed musical interventions within the US. Of the 25 studies, 72% reported a significant decrease in BP after the administration of a musical intervention and only 28% reported the race and ethnicity of participants.There are limited studies that examine the effect of music interventions on BP reduction in the US, as a primary outcome. However, based on the evidence, musical interventions are effective for BP reduction. Moreover, the studies that were conducted in the US include a low percentage of high-risk racial and ethnic minority populations. Future EBI should target this underserved/high-burden group to improve disparity gaps within BP reduction via non-pharmacological means.The review protocol is registered in Open Science Framework (DOI 10.17605/OSF.IO/4G3EB).